If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 11x^{2}+ -2x + 9 = 0 Reorder the terms: 9 + -2x + 11x^{2}= 0 Solving 9 + -2x + 11x^{2}= 0 Solving for variable 'x'. Begin completing the square. Divide all terms by 11 the coefficient of the squared term: Divide each side by '11'. 0.8181818182 + -0.1818181818x + x^{2}= 0 Move the constant term to the right: Add '-0.8181818182' to each side of the equation. 0.8181818182 + -0.1818181818x + -0.8181818182 + x^{2}= 0 + -0.8181818182 Reorder the terms: 0.8181818182 + -0.8181818182 + -0.1818181818x + x^{2}= 0 + -0.8181818182 Combine like terms: 0.8181818182 + -0.8181818182 = 0.0000000000 0.0000000000 + -0.1818181818x + x^{2}= 0 + -0.8181818182 -0.1818181818x + x^{2}= 0 + -0.8181818182 Combine like terms: 0 + -0.8181818182 = -0.8181818182 -0.1818181818x + x^{2}= -0.8181818182 The x term is -0.1818181818x. Take half its coefficient (-0.0909090909). Square it (0.008264462808) and add it to both sides. Add '0.008264462808' to each side of the equation. -0.1818181818x + 0.008264462808 + x^{2}= -0.8181818182 + 0.008264462808 Reorder the terms: 0.008264462808 + -0.1818181818x + x^{2}= -0.8181818182 + 0.008264462808 Combine like terms: -0.8181818182 + 0.008264462808 = -0.809917355392 0.008264462808 + -0.1818181818x + x^{2}= -0.809917355392 Factor a perfect square on the left side: (x + -0.0909090909)(x + -0.0909090909) = -0.809917355392 Can't calculate square root of the right side. The solution to this equation could not be determined.

| 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 | | 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 | | 3x^2+12x=180 | | 4x^2+13x-75=0 | | 4x^2+13-75=0 | | 3x^2+10x-88=0 | | 2v^2-4v+52= | | v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 | | 5x^2=13x+6 | | x^2+10x+25=0 | | X^2+4x+4=0 | | x^2+6x+9=0 | | -4x=2x^2-6 | | -x=2x^2-6 | | -2x=3x^2-1 | | -9x=2x^2-5 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions